Noncanonical Cell Fate Regulation by Bcl-2 Proteins. Issue 7 (July 2020) - Chong, Stephen Jun Fei; Marchi, Saverio; Petroni, Giulia; Kroemer, Guido; Galluzzi, Lorenzo; Pervaiz, Shazib
Abstract : Bcl-2 proteins are widely known as key controllers of mitochondrial outer membrane permeabilization, arguably the most important step of intrinsic apoptosis. Accumulating evidence indicate that most, if not all, members of the Bcl-2 protein family also mediate a number of apoptosis-unrelated functions. Intriguingly, many of these functions ultimately impinge on cell fate decisions via apoptosis-dependent or -independent mechanisms, delineating a complex network through which Bcl-2 family members regulate cell survival and death. Here, we critically discuss the mechanisms through which Bcl-2 proteins influence cell fate as they regulate autophagy, cellular senescence, inflammation, bioenergetic metabolism, Ca 2+ fluxes, and redox homeostasis. Highlights: The Bcl-2 protein family is widely known for controlling mitochondrial outer membrane permeabilization (MOMP), a key step in apoptotic cell death. Most, if not all, Bcl-2 family members have been shown to influence cellular processes apparently unrelated to apoptosis. Regulation of autophagy, cellular senescence, inflammation, bioenergetic metabolism, Ca 2+ fluxes, and redox homeostasis by Bcl-2 proteins ultimately impacts on cell fate. Modulating the Bcl-2 protein family holds promise as a potential therapeutic approach for numerous diseases beyond cancer.